Antileishmanial and lung adenocarcinoma cell toxicity of Withania somnifera (Linn.) dunal root and fruit extracts. Issue 16 (29th July 2022) - Orabi, Mohamed A. A.; Zidan, Sabry A. H.; Sakagami, Hiroshi; Murakami, Yukio; Ali, Ashraf A.; Alyami, Hamad S.; Alshabi, Ali Mohamed; Matsunami, Katsuyoshi
Abstract: This study aims to evaluate the anti- Leishmania major and the lung adenocarcinoma (A549) cytotoxicity of Withania somnifera root and fruit. The total extracts were obtained by homogenisation in aqueous MeOH, and the sub-extracts [ n -hexane, ethyl acetate (EtOAc), n -butanol ( n -BuOH), and methanol (MeOH)] were obtained by flash chromatography. The activity evaluation showed that n -BuOH sub-extracts from root and fruit exhibited noticeable antileishmanial promastigote properties. The n -hexane and EtOAc sub-extracts from both organs, and the MeOH sub-extract from the fruit exerted mild to moderate effects on the promastigotes. In-vitro growth-inhibitory test results on axenic amastigote and cytotoxicity testing on macrophages (RAW264.7), the parasite-host at the amastigote stage, revealed that the activity was mainly concentrated in the root EtOAc and n -BuOH sub-extracts and to a lesser extent the fruit MeOH and EtOAc, and the root n -hexane sub-extracts. Only the roots' EtOAc and n -BuOH sub-extracts demonstrated low cytotoxicity on the A549 cell line. Graphical Abstract: UF0001